Comparison of ITU-R predicted rainfall rates against measured data in Malaysia - Khairolanuar, Muhamad Haziq; Ismail, Ahmad Fadzil; Jusoh, Ahmad Zamani; Khan, Sheroz; Alam, A. H. M. Zahirul (2014)
This paper presents assessments of ITU’s predicted rainfall intensities against measurements acquired from a campaign in Kuala Lumpur, Malaysia. Data for a period of twenty months were collected between 1996 and 1998. The statistical analyses involve generation of annual cumulative distributions. Predicted values generated using established ITU- R rainfall intensity prediction models are compared with measurements, in order to test the validity of each model. Based on the comparison between the available rainfall intensity models, it can be suggested that the locally measured rainfall intensity annual cumulative distribution falls within the ITU-R climatic zone P, as suggested by the earliest ITU-R P.837-1 recommendation.